overview of ISO 9000 Based QMS Beneficial for Engineering Educational Institutions - Junnarkar, N. D. (Journal of Engineering Education Transformations, 2007)
With an increasing concern about the quality of engineering education being offered to the students, there is a need for a system of quality assurance in an educational institution. The establishment of ISO 9000 compliant quality systems represents one such methodology. This paper presents an overview of the ISO 9000 standards and provides information of the latest version of ISO 9000 (ISO 900J :2000) and how it is more acceptable to education. A general methodology for implementing ISO 9000 QMS in an educational Institution is presented. The reasons for certification, benefits and limitation faced in getting the ISO 9000 certification have been discussed ,based on experience and the research literature available which can help Institutions going for ISO 9000 certification to progress on this path.